Transforming rural agriculture Farmer FIRST Programme’s success in Khordha district - Mohapatra, Akankshya; Banu, H.; Debbarma, J.; Mahapatra, A. S.; Mohanty, S. K.; Das, K. S.; De, H. K. (Indian Farming, 2025)
The Farmer FIRST Programme, launched by ICAR-Central Institute of Freshwater Aquaculture, Bhubaneswar in 2016, is an innovative extension approach that integrates advanced technologies directly into farmers’ fields, enhancing agricultural productivity and livelihoods. By emphasizing practical application and fostering direct interaction between farmers and scientists, the programme ensures that technological solutions are adapted to real-world conditions and farmer feedback is incorporated. This collaborative effort prioritizes farmers’ resources and innovations, resulting in significant improvements in the adopted villages and contributing to better livelihoods for farmers and farm women.